Financial management of the enterprise in the conditions of crisis: economical and legal aspect - M. N. Dudin; E. E. Frolova (Путеводитель предпринимателя)
The global financial and economic crisis of2008-2010 has heightened interest in the issue of crisis management. This interest is manifested both at the level of individual enterprises and the economy as a whole. At the same time revealed a significant drawback: the development of the theory of crisis management lags behind practice. The discrepancy between the existing theory to modern requirements leads to the fact that well-known approaches based on theoretical concepts and the empirical facts and developments, and, therefore, are not systematic, in view of this further research is required in this direction.